2011
DOI: 10.1302/0301-620x.93b5.24883
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ankle foot orthoses with foot abduction orthoses to prevent recurrence following correction of idiopathic clubfoot by the Ponseti method

Abstract: The Ponseti method of clubfoot management requires a period of bracing in order to maintain correction. This study compared the effectiveness of ankle foot orthoses and Denis Browne boots and bar in the prevention of recurrence following successful initial management. Between 2001 and 2003, 45 children (69 feet) with idiopathic clubfeet achieved full correction following Ponseti casting with or without a tenotomy, of whom 17 (30 clubfeet) were braced with an ankle foot orthosis while 28 (39 clubfeet) were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 16 publications
1
77
0
2
Order By: Relevance
“…Some reports considered recurrence of clubfoot after treatment using the Ponseti method as any deformity that required additional casting and/or surgical intervention. This is almost similar to the definition of the Iowa group 3,6,14,25,26)…”
Section: Relapse After Full Correction and Non-compliance With Brace supporting
confidence: 78%
See 2 more Smart Citations
“…Some reports considered recurrence of clubfoot after treatment using the Ponseti method as any deformity that required additional casting and/or surgical intervention. This is almost similar to the definition of the Iowa group 3,6,14,25,26)…”
Section: Relapse After Full Correction and Non-compliance With Brace supporting
confidence: 78%
“…Many studies suggested that non-compliance with the brace treatment was closely associated with recurrence of the deformity 3,6,10,13,14,15,16,21,22,25,26,27). In addition, a few researches suggested that low educational level of parents, annual family income of < US $20,000, and Native American ethnicity were all significant risk factors for the recurrence of deformity following correction with the Ponseti method 3,14,15,21).…”
Section: Relapse After Full Correction and Non-compliance With Brace mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, using the appropriate orthosis is equally as important. A study comparing a Denis Brown orthosis with an ankle foot orthosis reveals that patients wearing the Denis Brown orthosis have significantly fewer recurrences [22]. However, Hemo et al, find no significant difference between Denis Brown and Mitchell braces after a minimum two-year follow-up period [23].…”
Section: Citation: Sayit E Sayit At (2015) Clinical Experiences and mentioning
confidence: 99%
“…19 Janicki et al also reported 31%.recurrence that required additional treatment. 24 None of the foot in our study required conversion or open tenotomy. There was no skin/soft tissue infection in any of our cases.…”
Section: Resultsmentioning
confidence: 78%